Impact of a maternal history of childhood abuse on the development of mother-infant interaction during the first year of life - Fuchs, Anna; Resch, Franz; Kaess, Michael (Child abuse & neglect, 2015)
The aim of this study was to examine the impact of a maternal history of abuse on mother-infant interaction (emotional availability; EA) in infancy and early toddlerhood. Over an 18-month period, women giving birth to a child in the local obstetric units were screened using the Childhood Trauma Questionnaire. Women who reported moderate or severe sexual and/or physical abuse were included in the maltreatment group (n=58; MG) and compared with a non-maltreated comparison group (n=61; CG). EA was investigated under experimental conditions when the children were 5 and 12 months of age using the Emotional Availability Scales. While mother-child dyads in the MG showed only very discrete interactional alterations at an infant age of 5 months, their EA differed significantly from the CG at 12 months due to the lack of an increase in EA observed in the MG. Exploratory analyses showed an additional effect of emotional abuse on EA at 12 months. These data indicate that the period when child locomotion develops might represent a critical time window for mothers with a history of abuse. Our results constitute an advance in research on child abuse as they identify a possible time window of non-normative alteration in mother-child interaction. This period could be targeted by strategies to prevent intergenerational transmission of abusive experiences.
Gesehen am 30.06.2020